2007
DOI: 10.1038/oby.2007.300
|View full text |Cite
|
Sign up to set email alerts
|

Designer Schools: The Role of School Space and Architecture in Obesity Prevention

Abstract: GORMAN, NICHOLAS, JEFFERY A. LACKNEY, KIMBERLY ROLLINGS, AND TERRY T.-K. HUANG. Designer schools: the role of school space and architecture in obesity prevention. Obesity. 2007;15:2521-2530. Spatial features of obesogenic environments studied on a broad community level have been associated with childhood overweight and obesity, but little research has focused on the effects of the design of micro spaces, such as schools, on individual health behaviors. This article aims to generate thinking and research on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 38 publications
0
22
0
1
Order By: Relevance
“…The FA composition of imported cooking oil was changed to contain higher amounts of polyunsaturated fat instead of saturated fat. The mean TC concentration decreased from 225 mg/dL in 1987 to 182 mg/dL in 1992, decreasing the prevalence of hypercholesterolemia from 25% to 6% in men and from 22% to 5% in women (107,108). This intervention was a classic example of a population-based strategy that effectively shifted the entire distribution of risk.…”
Section: Population-based Nutrition Interventions In College Studentsmentioning
confidence: 89%
“…The FA composition of imported cooking oil was changed to contain higher amounts of polyunsaturated fat instead of saturated fat. The mean TC concentration decreased from 225 mg/dL in 1987 to 182 mg/dL in 1992, decreasing the prevalence of hypercholesterolemia from 25% to 6% in men and from 22% to 5% in women (107,108). This intervention was a classic example of a population-based strategy that effectively shifted the entire distribution of risk.…”
Section: Population-based Nutrition Interventions In College Studentsmentioning
confidence: 89%
“…approach in Canada (Naylor et al, 2008) and the Belgian community school pilot project for increasing pupils' opportunities for PA (De Martelaer et al, 2002), the framework (see Figures 1 and 2) recommends that the PA team cooperates with external partners from the community and regional level, which are described later in the paper. The PA team could take action to expand cooperative PA programs and increase the connectivity with the neighborhood by opening up the school's play grounds and facilities to local sociocultural organizations promoting lifetime PA, sports clubs, and the community in general (Gorman, Lackney, Rollings, & Huang, 2007). Considering that a large majority of children attend schools, the PA team could regularly inform pupils about school-community partnerships with special attention to informing different at-risk populations.…”
Section: Main Organizational and Policy Features At The Community Levmentioning
confidence: 99%
“…A one percentage point increase in minority student population, however, was associated with a 0.34% reduction in FV percentage consumed (Table 7; p  < .05). This result suggested that, although schools with higher participation in FRPM may serve more FV due to stronger wellness policies [13, 56], environmental variations captured by CAFES items, food quality, food preferences, role modeling, or nutrition education [57, 58] may contribute to lower FV percentages consumed in schools with larger percentages of minority students.…”
Section: Resultsmentioning
confidence: 99%